Migration processes and their impact on the russian labor market ("Journal "U". Economy. Management. Finance.", 2025)
The article examines migration processes, which are an important factor in the formation of the modern Russian labor market, exerting both a positive influence on it and creating certain challenges. Analysis of these aspects allows us to better understand the dynamics of the labor market in the context of external and internal migration activity.
Keywords: migration processes; labor market